Jainism before 650 BCE - Jain, Shugan C.; Pandey, Shrinetra (International School fpr Jain Studies, 2020)
Papers presented at the Two days International Seminar on "Traces of Śhramaṇa Tradition (With Special Reference to Jainism): Prior To 650 BCE" organized by International School for Jain Studies (ISJS), New Delhi in association with Bhandarkar Oriental Research Institute (BORI), Pune on 5-6 October, 2019. Sponsored by Shri Firodia Trust, Pune